A nested case-control study of lung cancer among silica exposed workers in China. Issue 3 (March 1992) - McLaughlin, J K; Chen, J Q; Dosemeci, M; Chen, R A; Rexing, S H; Wu, Z; Hearl, F J; McCawley, M A; Blot, W J
Abstract : In an attempt to assess whether silica induces lung cancer, a nested case-control study of 316 male lung cancer cases and 1352 controls was carried out among pottery workers and tungsten, copper-iron, and tin miners from five provinces in south central China. Exposure to dust and silica for each study subject was evaluated quantitatively by cumulative exposure measures based on historical industrial hygiene records. Measurements on confounders such as inorganic arsenic, polycyclic aromatic hydrocarbons (PAHs), and radon were also collected from the worksites. Information on cigarette smoking was obtained by interviews of the subjects or their next of kin. A significant trend of increasing risk of lung cancer with exposure to silica was found for tin miners, but not for miners working in tungsten or copper-iron mines. Concomitant and highly correlated exposures to arsenic and PAHs among tin miners were also found. Risk of lung cancer among pottery workers was related to exposure to silica, although the dose-response gradient was not significant. Risks of lung cancer were significantly increased among silicotic subjects in iron-copper and tin mines, but not in pottery factories or tungsten mines. The results of this study provide only limited support for an aetiological association between silica and lung cancer.